Proceedings of the Fourth International Conference in Ocean Engineering (ICOE2018) Volume 2 - Murali, K.; Sriram, V.; Samad, Abdus; Saha, Nilanjan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprises selected proceedings of the Fourth International Conference in Ocean Engineering (ICOE2018), focusing on emerging opportunities and challenges in the field of ocean engineering and offshore structures. It includes state-of-the-art content from leading international experts, making it a valuable resource for researchers and practicing engineers alike. .
Port, Harbour and Coastal Structures -- Offshore Structures and Deepwater Technology -- Marine Foundations and Reclamation -- Marine Vehicles and Floating Systems -- AUVs, ROVs and Underwater Systems -- Ocean Optics & Acoustics, GIS and Satellite Imaging -- Petroleum Engineering & Technology -- Climate Change and its Impacts -- Ocean Renewable Energy -- Marine and Coastal Hydrodynamics -- Computations in Ocean and Petroleum Engineering -- Safety, Risk and Reliability Including Environment.
Keywords: Offshore structures; Oceanography; Mechanics, Applied; Solids; Fire prevention; Buildings -- Protection; Offshore Engineering; Ocean Sciences; Solid Mechanics; Fire Science, Hazard Control, Building Safety